Scholarship 2.0: analyzing scholars’ use of Web 2.0 tools in research and teaching activity - Calvi, Licia; Cassella, Maria (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2013)
Over the past 15 years the Web has transformed the ways in which we search for information and use it. In more recent years, we have seen the emergence of a new array of innovative tools that collectively go under the name of ‘Web 2.0’, in which the information user is also increasingly an information producer (i.e., prosumer), by sharing or creating content. The success of Web 2.0 tools for personal use is only partially replicated in the professional sphere and, particularly, in the academic environment in relation with research and teaching. To date, very few studies have explored the level of adoption of Web 2.0 among academic researchers in their research and teaching activity. It is not known in what way how and how much Web 2.0 is currently used within research communities, and we are not aware of the drivers and the drawbacks of the use of Web 2.0 tools in academia, where the majority of people is focused either on research or on teaching activities. To analyse these issues, i.e. the combined adoption of Web 2.0 tools in teaching and research, the authors carried out a survey among teaching and researching staff of the University of Breda in The Netherlands. This country was chosen mainly because it is on the cutting edge as far as innovation is concerned. An important driver in choosing the Breda University’s academic community was the fact that one of the two authors of this survey works as senior researcher at this university. The purpose of our survey was to explore the level of adoption of Web 2.0 tools among the academic communities. We were interested in investigating how they were using these tools in the creation of scientific knowledge both in their research and teaching activity. We were also interested in analysing differences in the level of adoption of Web 2.0 tools with regard to researchers’ position, age, gender, and research field. Finally, in our study we explored the issue of peer reviewing in the Web 2.0 setting. In particular, we investigated whether social peer review is regarded by researchers as a viable alternative to the current closed peer review system (single-blind or double blind). We approached about 60 staff members, but only 12 faculty members completed the survey fully. This means that our results can only be regarded as exploratory, but we still believe that they represent a complementary perspective with respect to previous studies.